2021
DOI: 10.1371/journal.pone.0254128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between average daily rehabilitation time and decline in instrumental activity of daily living among older patients with heart failure: A preliminary analysis of a multicenter cohort study, SURUGA-CARE

Abstract: Background Limitation of instrumental activity of daily living (IADL) is independently associated with an adverse prognosis in older heart failure (HF) patients. Aims This multicenter study aims to examine the relationship between average daily rehabilitation time (ADRT) and risk of IADL decline during acute hospitalization in older patients with HF. Methods Four hundred eleven older patients who were hospitalized due to acute HF and underwent rehabilitation were divided into three groups based on the tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The result of multivariable analysis indicated that non-lying time was selected as independent related factor of the HAFD after adjustment for propensity score. Although an association between HAFD and in-hospital physical activity including step count [ 7 ] and rehabilitation time [ 8 ] has previously been reported in heart failure patients, the association with non-lying time has not been addressed. A possible explanation for this finding may be that sitting/standing posture reduced the risk of muscle weakness including iatrogenic sarcopenia, a major hospital-acquired comorbidity caused by excessive bed rest in an acute phase clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of multivariable analysis indicated that non-lying time was selected as independent related factor of the HAFD after adjustment for propensity score. Although an association between HAFD and in-hospital physical activity including step count [ 7 ] and rehabilitation time [ 8 ] has previously been reported in heart failure patients, the association with non-lying time has not been addressed. A possible explanation for this finding may be that sitting/standing posture reduced the risk of muscle weakness including iatrogenic sarcopenia, a major hospital-acquired comorbidity caused by excessive bed rest in an acute phase clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies demonstrated that lower physical activity, especially daily step counts, and shorter rehabilitation time is possible risk factor for HAFD [ 7 , 8 ]. The link between the amount of physical activity and HAFD implies that early mobilization and enhancing physical activity during hospitalization may be effective in preventing HAFD.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, the management of frailty is essential for elderly patients with HF. As recent research has shown that appropriate rehabilitation implementation can prevent a decline in activities of daily living in elderly patients with HF (35), early and active rehabilitation may help prevent physical frailty, which is a risk factor for poor outcomes in elderly patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…We retrieved the average frequency and duration of PT per week from the medical records and compared them to those reported by previous studies of patients with HF, Kato et al reported that the median length of hospital stay was 21 days, and the median number of rehabilitation days was 9 for the intermediate group 16) . Takahashi et al reported that the median duration of rehabilitation was 7 days, and the median total unit of rehabilitation was 15 (where 1 unit = 20 minutes) 18) .…”
Section: Average Frequency and Duration Of Pt Per Weekmentioning
confidence: 99%
“…Therefore, it is necessary to determine the different effects of frequency and duration of PT on ADLs in patients with HF. A study investigating these associations in hospitalized geriatric patients with acute HF suggested that shorter average daily rehabilitation times may increase the risk of a decline in instrumental ADLs during hospitalization 16) . Nevertheless, no studies have investigated the relationship between the frequency and duration of PT and basic ADLs, which are widely used as a definition of HAD.…”
Section: Introductionmentioning
confidence: 99%